2020
DOI: 10.3390/ijms21030851
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Adaptations upon Recruitment to the Lung: New Concepts and Implications for Homeostasis and Disease

Abstract: Neutrophils have a prominent role in all human immune responses against any type of pathogen or stimulus. The lungs are a major neutrophil reservoir and neutrophilic inflammation is a primary response to both infectious and non-infectious challenges. While neutrophils are well known for their essential role in clearance of bacteria, they are also equipped with specific mechanisms to counter viruses and fungi. When these defense mechanisms become aberrantly activated in the absence of infection, this commonly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 185 publications
(194 reference statements)
1
60
1
1
Order By: Relevance
“…Several changes resulted from elastase administration such as disorganized elastin, degradation of proteoglycans, and abnormal collagen remodeling. Regarding the dose and number of elastase challenges, many scientific groups demonstrated that mice subjected to five elastase administrations with a 1-week interval between them developed not only a more severe alveolar destruction, but also systemic manifestations, such as diaphragmatic dysfunction, weight loss, pulmonary arterial hypertension, and exercise intolerance (De et al, 2016;Crocetti et al, 2019;Giacalone et al, 2020). Thus, inhibition of elastase by chemical drugs has also been suggested as a way to recover from different inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several changes resulted from elastase administration such as disorganized elastin, degradation of proteoglycans, and abnormal collagen remodeling. Regarding the dose and number of elastase challenges, many scientific groups demonstrated that mice subjected to five elastase administrations with a 1-week interval between them developed not only a more severe alveolar destruction, but also systemic manifestations, such as diaphragmatic dysfunction, weight loss, pulmonary arterial hypertension, and exercise intolerance (De et al, 2016;Crocetti et al, 2019;Giacalone et al, 2020). Thus, inhibition of elastase by chemical drugs has also been suggested as a way to recover from different inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical trials revealed an insufficient therapeutic efficacy of the drug in human severe lung injury and respiratory inflammation (Zeiher et al, 2004). Additionally, sivelestat has the risks of organ toxicity and poor pharmacokinetics (Tsai et al, 2015;Giacalone et al, 2020). The problem in developing new elastase inhibitors is the interference function of elastase with other proteases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sepsis-induced ALI, neutrophils are recruited and primed in the injury site by insults released from activated residential cells in circulation, 3 which subsequently clear the pathogen by efferocytosis, NETosis and proteinases. 4,5 However, the excessive accumulation of primed neutrophils contributes to uncontrolled inflammation and extreme lung damage, which are correlated with poor clinical outcome in ARDS. [6][7][8] In animal models, the depletion of neutrophils reduces the severity of lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are immune cells whose function is absolutely necessary for an efficient defensive response, nevertheless, an increase in neutrophil recruitment or a failure in their clearance is associated with collateral tissue damage, delayed or defective healing, and non-resolved inflammation [1,2]. For example, chronic inflammation as observed in cystic fibrosis (CF), non-eosinophilic asthma or chronic obstructive pulmonary disease (COPD), as well as acute inflammatory responses including Covid-19 are often affected by massive neutrophilic infiltration, thus its contention appears necessary [3][4][5][6]. In fact, animal models of acute lung injury (ALI) have provided insight as neutrophil depletion, or inhibition of neutrophil function, invariably ameliorates the extent of damage in the lungs [7].…”
Section: Introductionmentioning
confidence: 99%